Impact of the Covid-19 Outbreak on the Dental Profession in Pakistan - Tania Naveel, Daud Sultan, Hammal Khan Naseer Baloch, Asad Tahir, Bilal Ahmad, Naveed Ahmad Khan, Sana Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
The COVID-19 outbreak has affected dentists all over the world, including those in the Pakistan. It has had a huge impact on the practice of dental professionals as they are in direct contact with oral and nasal secretions of patients in the field. We conducted this study to find out how dental practitioners felt about the outbreak and how they believed it will affect the dental profession. To assess the impact of COVID-19 outbreak in Pakistan an exploratory cross-sectional study of dental professionals was conducted. Self-administered questionnaires were distributed to consenting participants between October and December 2021 via an online data collection platform (Google forms). These questionnaires were to collect the data about the understanding and awareness about the pandemics impact on respondent’s sociodemo graphics and psychological health. The data analysis in this study was done using the Statistical Package for the Social Sciences (SPSS) version 20. The study included 118 dental practitioners from the Pakistan, with an average age of 39.25 years and a majority of the participants were males. COVID 19 was determined to be well-understood by nearly 91 (77.1 %) respondents. COVID-19 was of the grave concern for more than half of the participants, 64 (54.24%), with the danger of catching the virus in the dentistry clinic being the most concerning cause of concern 64 (54.24%). It is concluded that the dental practitioners had an excellent awareness about the epidemiology, diagnosis, prevention, and treatment of COVID-19.